Nivel socioeconómico, hábitos alimentarios y estado nutricional en jóvenes del distrito de Punchana, Iquitos 2022 - Pérez Pinedo, Marisol Carolina (2023)
The purpose of this study was to determine the correlation between socioeconomic status, eating habits and nutritional health of young people in the Punchana district of Maynas province, Loreto department. A descriptive correlational non-experimental study was carried out and cross-sectional data were collected from three hundred young people. It was determined, through the use of questionnaires on frequency of food consumption, socioeconomic level and anthropometric evaluation, 64.6% reported low socioeconomic level, 33.1% medium level and 2.3% high level; 77.6% have unhealthy eating habits, 17.7% unhealthy and 4.7% healthy eating habits. Likewise, 52.3% of the sample had a moderate risk of suffering cardiometabolic diseases, 31.1% a high risk and 16.7% a very high risk. At a statistical confidence of 95%, the relationship between eating habits and nutritional status is statistically significant, with a p-value of 0.002 and a Kendall's tb coefficient of 0.765. Similarly, with a p-value of 0.000 and a Kendall's tb coefficient of 0.315, it can be affirmed that there is a very low relationship between socioeconomic level y nutritional status.